MARKETING STRATEGIES IN INCREASING SALES AT NUSANTARA BOOKSTORE IN THE DIGITAL ERA - Kirana, Bayu; Kurnia M, Fakhrudddin (Jurnal Manajemen Dan Bisnis, 2024)
This study explores the challenges faced by Toko Buku Nusantara in the digital era. Technology has transformed how consumers shop and access information, requiring traditional bookstores to find innovative ways to stay relevant and competitive. The research employs a literature study method to analyze changes in marketing strategies in response to digital challenges, highlighting the importance of understanding the ever-changing consumer preferences. Innovative and creative marketing strategies are necessary to address changes in consumer behavior, industry dynamics, and technological advancements. The study found that Toko Buku Nusantara experienced a decline in sales from 2018 to 2023 due to consumers becoming more critical and savvy in price comparison. Intense competition with book producers and publishers, along with changes in government policies, pose additional challenges. It is recommended that Toko Buku Nusantara utilize online marketplaces and social media platforms to expand market reach and enhance customer loyalty. Digital transformation also demands a culture of innovation and collaboration with external parties. Future business success not only depends on technology but also on the ability to innovate, adapt, and understand market dynamics. With the right strategies, Toko Buku Nusantara can strengthen its market position, ensure business sustainability, and remain competitive in the ever-evolving digital era